2003
DOI: 10.1051/0004-6361:20030805
|View full text |Cite
|
Sign up to set email alerts
|

A fourth component in the young multiple system V 773 Tauri

Abstract: Abstract. I report on a new component in the pre-main sequence multiple system V 773 Tauri. This second visual companion, V 773 Tau C, with a projected separation of ≈0. 2 has been detected using speckle interferometry in the near-infrared. Repeated observations from 1996 to 2002 show significant orbital motion and thus confirm the character of the new companion as a gravitationally bound star. Together with the two components of the spectroscopic binary V 773 Tau A and the previously known visual companion V … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…V773Tau is a well-known quadruple system (see, e.g., Duchêne et al 2003;Woitas 2003), and the source detected in our observations is the primary component V773TauA, which itself is a tight binary. V773TauA has been detected in a total of seven epochs during our observing, but a simultaneous detection of both components occurred only in three epochs (see Table 4).…”
Section: V773taumentioning
confidence: 54%
“…V773Tau is a well-known quadruple system (see, e.g., Duchêne et al 2003;Woitas 2003), and the source detected in our observations is the primary component V773TauA, which itself is a tight binary. V773TauA has been detected in a total of seven epochs during our observing, but a simultaneous detection of both components occurred only in three epochs (see Table 4).…”
Section: V773taumentioning
confidence: 54%
“…A fourth member of this system, V773 Tau D, has an angular separation of ∼0. 22 with respect to V773 Tau A (Woitas 2003) and it has been classified as an infrared companion due to the shape of its SED (Duchêne et al 2003). These objects are believed to be T Tauri stars embedded in dusty envelopes and undergoing episodes of intense accretion.…”
Section: Discussionmentioning
confidence: 99%
“…A is a shortperiod (51 days) double-lined spectroscopic binary (Welty 1995). In addition, Duchene et al (2003) and Woitas (2003) identified an additional infrared component (C) within 0 3 from A. g Cieza et al (2013) report excess at wavelengths longer than 24 μm for V1321…”
Section: Observations and Data Reductionmentioning
confidence: 96%